APPROCHE SOCIOLOGIQUE DE LA QUESTION DES INEGALITES D’ACCES AUX SOINS EN ALGERIE - BOULEDROUA, Abdelkkrim (Journal of Human Sciences, 2017)
From a multiple sources of information on official statistics and major health surveys carried out in Algeria between 1990 and 2006, this article examines the health situation in Algeria on the issue of unequal access to healthcare, which is the result of all Social inequalities in health; It includes, among others, the elements of a field survey carried out by the author in 2007 with households around the difficulties / facilities to seek treatment and access to care.